ANALISIS PENERAPAN E-GOVERNMENT SISTEM KEPENDUDUKAN INFORMASI DAN LAYANAN (SIPENDIL) DALAM PELAYANAN PUBLIK DI DESA SITIWINANGUN KECAMATAN JAMBLANG KABUPATEN CIREBON - Subhan Subhan; Annisa Rengganis; Serin Andrayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2021)
This study aims to determine the E-Government Application of Population Services and Information Systems in Public Services in Sitiwinangun Village, Jamblang District, Cirebon Regency.This research method is descriptive research with a qualitative approach. Data was collected using observation, interviews, and documentation. Researchers used data triangulation and source triangulation to check the validity of research data. Data analysis in this study uses three components consisting of data reduction, data presentation, and concluding.The results showed that the E-Government Application of Population Services and Information Systems in Public Services in Sitiwinangun Village, Jamblang District, Cirebon Regency had implemented the dimensions of Support, Value/Value and Ability/Capacity along with their indicators.The people of Sitiwinangun Village, Jamblang District, as users of the Public Service Population Service and Information System application, are satisfied with the services provided by the service officers at the Sitiwinangun Village Office, Jamblang District, Cirebon Regency. But not many people use the application due to the lack of more intensive socialization to the community.